Central µ-opioidergic system activation evoked by heavy and severe-intensity cycling exercise in humans: a pilot study using positron emission tomography with 11C-carfentanil - Hiura, M.; Sakata, M.; Ishii, K.; Toyohara, J.; Oda, K.; Nariai, T.; Ishiwata, K. (International Journal of Sports Medicine, 2017)
The central opioid receptor system likely contributes to the mechanism underlying the changes in affect elicited by exercise. Our aim was to use positron emission tomography (PET) to test whether exercise intensity influences activation of the µ-opioid receptor system in the brain, and whether changes in opioid receptor activation correlate with exercise-induced changes in affect. 7 healthy young male subjects (23±2 years) performed 20-min constant-load cycling exercises at heavy (ExH) and severe-intensity (ExS), and PET was performed using [11C]carfentanil as a tracer before and after each exercise. Exercise elicited the µ-opioidergic system activation in the large areas of the limbic system, particularly in the insular cortex, and cerebellum. Of note, deactivation of the µ-opioidergic system in the pituitary gland was identified as a specific finding in ExS, which evoked a distinctive sensation of fatigue. Within these brain areas, µ-opioid receptor activation correlated positively with increased positive affect (R2=0.67-0.95) in ExH and negative affect (R2=0.63-0.77) in ExS. These findings suggest that central µ-opioidergic neurotransmission evoked by continuous exercise is discriminated by work intensity. Notably, we also observed a possible contribution of the central µ-opioidergic system to the development of the sensation of fatigue during exhaustive exercise.